2015
DOI: 10.1128/mcb.00541-15
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Lethal Interaction between Glutathione Synthesis and Mitochondrial Reactive Oxygen Species Provides a Tumor-Specific Vulnerability Dependent on STAT3

Abstract: e Increased production of mitochondrion-derived reactive oxygen species (ROS) is characteristic of a metabolic shift observed during malignant transformation. While the exact sources and roles of ROS in tumorigenesis remain to be defined, it has become clear that maintaining redox balance is critical for cancer cell proliferation and survival and, as such, may represent a vulnerability that can be exploited therapeutically. STAT3, a latent cytosolic transcription factor activated by diverse cytokines and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…2). This hypothesis is supported by data showing that pharmacological inhibition of GSH synthesis results in accumulated ROS, DNA damage and death in Ras-transformed, STAT3 expressing cell lines [53].…”
Section: Metabolic Activity Of Stat3 Co-operation Of Nuclear and Mitmentioning
confidence: 89%
See 1 more Smart Citation
“…2). This hypothesis is supported by data showing that pharmacological inhibition of GSH synthesis results in accumulated ROS, DNA damage and death in Ras-transformed, STAT3 expressing cell lines [53].…”
Section: Metabolic Activity Of Stat3 Co-operation Of Nuclear and Mitmentioning
confidence: 89%
“…Mitochondrial accumulation of STAT3 correlates with altered concentrations of Reactive Oxygen Species (ROS) [34,45,[52][53][54]. A mass-spectrometry based screen for mitochondrial-STAT3 dependent metabolites revealed that mitochondrial-STAT3 alters the glutathione (GSH) synthesis machinery [53].…”
Section: Metabolic Activity Of Stat3 Co-operation Of Nuclear and Mitmentioning
confidence: 99%
“…Constitutively acetylated STAT3 translocates into mitochondria, where it sustains altered TCA-ETC function for glycolytic and oxidative phosphorylation reactions. The STAT3-dependent metabolic regulation of pyruvate conversion in mitochondria supports Ras-dependent malignant transformation59.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the intriguing discovery was made that STAT3 associates with mitochondria and therein regulates electron transport chain function as well as glycolytic and oxidative phosphorylation [13, 48]. Mitochondrial STAT3 is also implicated in control of the gamma-glutamyl cycle, production of glutathione and regulation of reactive oxygen species (ROS) [49]. Furthermore, in embryonic stem (ES) cells, STAT3 controls mitochondrial gene expression and respiration, mechanisms that optimize ES cell proliferation and maintenance [50].…”
Section: Non-transcriptional Activities Of Stat3mentioning
confidence: 99%